Social psychology of emotion - Ellis, Darren; Tucker, Ian (Sage, 2015)
The study of emotion tends to breach traditional academic boundaries. It requires multi-modal perspectives and the suspension of dualistic conventions to appreciate its complexity. This book analyses historical, philosophical, psychological, biological, sociological, post-structural, and technological perspectives of emotion that Ellis and Tucker argue are important for a viable social psychology of emotion. It begins with early ancient philosophical conceptualisations of pathos and ends with analytical discussions of the transmission of affect which permeate the digital revolution. It will be of interest to upper level undergraduate and postgraduate students of psychosocial studies, the individual and society, and courses across the social sciences dealing with affect and emotion.-- Source other than the Library of Congress.